(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the therapeutic effects of electroacupuncture combined with therapeutic ultrasound and the Lục Vị formula in the treatment of knee osteoarthritis at Phu Tho Traditional Medicine and Rehabilitation Hospital, and to describe some undesirable effects of the treatment method. Subjects and Methods: A prospective clinical study with before–afterbefore–and–after comparison was conducted on 50 patients diagnosed with knee osteoarthritis of the Cold-Dampness obstruction type combined with Liver-Kidney deficiency. Patients were treated with a combined regimen of electroacupuncture, therapeutic ultrasound, and the Lục Vị decoction for 20 days. Treatment effectiveness was assessed based on changes in VAS pain score, WOMAC index (pain, stiffness, physical function), and clinical indicators (knee joint range of motion, heel–buttockheel–to–buttock distance) at three time points: before treatment (D0), day 10 (D10), and day 20 (D20). Results: After 20 days of treatment, the combined regimen showed significant improvement in all evaluated indicators. The mean VAS pain score decreased from 6.02 ± 0.14 to 2.32 ± 1.65 (p < 0.01). The total WOMAC score decreased from 55.66 ± 3.47 to 15.36 ± 4.94 (p < 0.01). The knee flexion range increased from 95.4 ± 7.61° to 111.5 ± 12.83° (p < 0.01). Other clinical symptoms of Traditional Medicine such as stiffness, joint crepitus, and poor sleep, such as stiffness, joint crepitus, and poor sleep, also improved significantly (p < 0.05). The treatment regimen was well toleratedwell-tolerated and safe. Conclusion: The combination of electroacupuncture, therapeutic ultrasound, and the Lục Vị formula is an effective and safe treatment that helps reduce pain, relieve stiffness, and significantly improve mobility in patients with knee osteoarthritis.